Managing engine thermal state to reduce friction losses during warm-up - Zammit, Jean-Paul (2013)
The thermal behaviour of a 2.4 l direct injection diesel engine has been investigated to identify how the fuel consumption penalty associated with operation during warm–up can be minimised. A version of PROMETS (Programme for Modelling Engine Thermal Systems) was developed to support the investigations. The developments improved the representation of thermal-friction conditions in the oil circuit, extended the piston heat transfer sub-model to account for the effects of piston cooling jets and introduced a main bearing thermal-friction model to predict friction and oil film temperatures. Computational studies were complemented by an experimental investigation of the effectiveness of pre-heating the oil feed to the bearings. Results show that heat transfer from the oil film to the bearings shells and crankshaft journal reduces the benefit in friction savings. Other measures considered were exhaust gas heat recovery, repositioning of the oil main gallery within the block, thermal energy storage, reductions in engine thermal capacity and a novel split-EGR cooler able to cool the EGR gases and heat either the coolant or oil streams. All of the above measures were investigated in isolation, but where appropriate different measures were adopted in conjunction to achieve even greater fuel savings.